Local haemorrhage induced by Bothrops jararaca venom: relationship to neurogenic inflammation - Luis Roberto C. Gonçalves; Mario Mariano (Hindawi Limited, 2000)
We investigated morphological alterations induced by s.c. injection of 2.5 μg of Bothrops jararaca venom in rats. Intense disorganisation of collagen fibres was observed 1 min after the venom injection, particularly at regions near vessels and nerves. Mast cells were degranulated, and erythrocytes were seen leaving venules throughout the endothelial junctions. At this time, damaged endothelial cells were not observed. In rats envenomed as above, but immediately after cardiorespiratory failure induced by deep ether anaesthesia, alterations in the connective tissue structures, as previously described, were not observed. The mediation of this haemorrhage was investigated by injecting the venom into the foot pad of mice and compared to the mediation of oedema. Local haemorrhage was significantly reduced in mice pre-treated with capsaicin or guanethidine or submitted to a surgical section of sciatic and saphenous nerves. In these animals, oedema was not affected. Groups treated with methysergide or morphine showed both haemorrhage and oedema significantly reduced. Indomethacin or dexamethasone pre-treatments significantly reduced the oedema, but not the haemorrhage. Moreover, in animals treated with promethazine or mepyramine, oedema and haemorrhage were not affected. These data suggest that local haemorrhage induced by Bothrops jararaca venom is partially controlled by serotonin and neurohumoral mediators. Furthermore, results indicate that haemorrhage and oedema are mediated by different pharmacological systems.